The influence of iron homoeostasis on macrophage function. (August 2002) - Ward, R. J.; Wilmet, S.; Legssyer, R.; Crichton, R. R.
Abstract : Iron loading of alveolar macrophages in vivo significantly altered their ability to respond to various inflammatory stimuli. This was exemplified by reduced synthesis of inducible nitric oxide synthase after stimulus with lipopolysaccharide and interferonγ, and an enhanced activation of nuclear factor k B in the absence of tumour necrosis factor α stimulation, and enhanced production of reactive oxygen species after activation with activated zymosan and PMA. Such results may indicate an imbalance in the production of reactive oxygen and reactive nitrogen species generated by